2022
DOI: 10.1177/13694332221104282
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies on the seismic responses of precast segmental columns-supported bridge structures subjected to near-fault ground motions

Abstract: Precast segmental columns have attracted wide attentions in bridge construction industry recently due to its ability to accelerate construction speed, improve construction quality and reduce environmental impact. It is of great practical importance to study the seismic performances of segmental columns, and many experimental and numerical studies have been performed. However, most previous studies focused on segmental column itself, the research on the seismic performance of a whole bridge structure supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…It was found the residual drift of the bridge with PSC column decreased about 80% and the peak drift demand increased about 17%. Li et al (2022) carried out numerical studies on the seismic responses of PSCs-supported bridge structures subjected to near-fault ground motions. It was concluded that the influence of permanent ground displacement on the PSCs-supported bridge is not evident but it could significantly influence the traditional monolithic columns-supported bridge.…”
Section: Bridge With Psc Piersmentioning
confidence: 99%
“…It was found the residual drift of the bridge with PSC column decreased about 80% and the peak drift demand increased about 17%. Li et al (2022) carried out numerical studies on the seismic responses of PSCs-supported bridge structures subjected to near-fault ground motions. It was concluded that the influence of permanent ground displacement on the PSCs-supported bridge is not evident but it could significantly influence the traditional monolithic columns-supported bridge.…”
Section: Bridge With Psc Piersmentioning
confidence: 99%